Introduction [In 2019 Annual trends and outlook report] - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Njuki, Jemimah (International Food Policy Research Institute, 2019)
Fifteen years ago, in July 2004, the heads of state and government of member states of the African Union signed a Solemn Declaration to reaffirm their commitment to gender equality in Africa (African Union 2004). Ten years later, the Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods set forth new goals for a more targeted approach to achieve the agricultural vision for the continent, which is shared prosperity and improved livelihoods (African Union 2014b). In a series of seven commitments, that declaration reconfirmed that agriculture is a critical sector for African economic growth and poverty reduction and should remain high on the development agenda of the continent. The Malabo Declaration affirmed the African Union’s resolve to ensure, through “deliberate and targeted public support,” that all segments of the African population, “women, the youth, and other disadvantaged sectors,” must “participate and directly benefit from the growth and transformation opportunities to improve their lives and livelihoods.” The commitment to halving poverty by 2025 through inclusive agricultural growth and transformation states that governments will support and facilitate preferential entry and participation for women and youth in gainful and attractive agribusiness opportunities (African Union 2014b). However, this is the only commitment to mention women explicitly, and as stated, it focuses on women as a single category, not in relation to men, their families, and communities.